No relation between adenosine triphosphate after manual cleaning and presence of microorganisms on endoscopes after automated high-level disinfection - Kwakman, Judith A.; Rauwers, Arjan W.; Buijs, Jolanda G.; de Groot, Woutrinus; Vos, Margreet C.; Bruno, Marco J. (Endoscopy International Open, 2022)
Background and study aims Adenosine triphosphate (ATP) tests are increasingly used to detect biological material; however, their reliability to detect bacterial contamination in endoscopes is not proven. We investigated the predictive value of ATP tests after manual cleaning for presence or absence of microorganisms as shown by culture after automated high-level disinfection (HLD) in duodenoscopes and linear echoendoscopes (DLEs).Patients and methods After manual cleaning, ATP tests were performed on swab samples taken from the detachable cap and forceps elevator, and on flush samples of the DLE working channels. These results were compared to the growth of any microorganisms in cultures acquired after automated HLD. ATP tests with > 200 relative light units (RLU) were considered positive. Receiver operator characteristic (ROC) curves were used to compare the RLU levels with microbial presence in cultures.Results In total, 903 procedures were performed involving 26 distinct DLEs. Depending on sample site, 20.8 % (cap) to 63.8 % (channel brush) of the ATP negative samples were accompanied by positive post-HLD cultures. 54.4 % of the cap samples with a positive culture (growth of any kind of microorganism) and 91.8 % of the channel samples with a positive culture had a negative ATP test after manual cleaning. ROC curves per sample site, DLE type and microorganism type all had area under the curves below 0.6.Conclusions In our study, ATP tests performed after manual cleaning could not predict presence or absence of microorganisms after automated HLD as shown by culture. More than half of the positive cultures were preceded by a negative ATP test.